Health Disparities Among Indigenous Peoples: Exploring the Roles of Evolutionary and Developmental Mismatch on Cardiometabolic Health - Gurven, Michael; Lea, Amanda; Sarrieddine, Ayana (Annual Review of Anthropology, 2024)
The health of Indigenous populations suffers compared with that of non-Indigenous neighbors in every country. Although health deficits have long been recognized, remedies are confounded by multifactorial causes, stemming from persistent social and epidemiological circumstances, including inequality, racism, and marginalization. In light of the global morbidity and mortality burden from heart disease, stroke, and diabetes, cardiometabolic health needs to be a target for building scientific understanding and designing health outreach and interventions among Indigenous populations. We first describe health disparities in cardiometabolic diseases and risk factors, focusing on Indigenous populations outside of high-income contexts that are experiencing rapid but heterogeneous lifestyle change. We then evaluate two evolutionary frameworks that can help improve our understanding of health disparities in these populations: (a) evolutionary mismatch, which emphasizes the role of recent lifestyle changes in light of past genetic adaptations, and (b) developmental mismatch, which emphasizes the long-term contribution of early-life environments to adult health and the role of within-lifetime environmental change.
Keywords: Cardiometabolic Disease; Diabetes; Evolutionary Mismatch; Heart Disease; Indigenous Health